Perspectives of community-dwelling older adults with dementia and their carers regarding their oral health practices and care: rapid review - S. KC; M. Aulakh; S. Curtis; S. Scambler; J. E. Gallagher (Nature Publishing Group, 2021)
Abstract Aim To review evidence on oral health practices, beliefs/views and experiences of community-dwelling older adults living with dementia, including their carers. Materials and methods A search of key terms across six databases including Pubmed, Web of Science and OVID (Embase, MEDLINE [R] and PsycINFO) and Google Scholar was conducted, supplemented by reference screening. The Mixed Methods Appraisal Tool (MMAT) 2018 was used to assess the methodological quality. Results Eighteen studies reported across 19 papers were included in the review. Papers largely focused on normative needs (n = 13), whilst also reporting oral health-related experiences (n = 2), practices (n = 7), and beliefs/views (n = 9), of community dwellers with dementia. Generally, people living with dementia presented with poor oral and dental health, the exception being one study where dental care was integrated with memory clinic services. Maintenance of oral health focused only on toothbrushing. Overall, people living with dementia have reduced capacity for self-performed oral hygiene and high reliance on caregivers. There was a paucity of evidence on their perceptions of oral health and quality of life, the findings of which were equivocal, with weak evidence suggesting possible difficulty in identifying and communicating their needs. Experiences of accessing dental care, when explored, appear to be system dependent. Conclusion There was limited research evidence on oral health-related practices, beliefs/views and experiences of people with dementia. Recommendations for future research are presented.